Prototypes without design? - Kapustin, Petr (project baikal, 2021)
The problematics of succession and innovations in architecture cannot be discussed beyond the prototype category. It is a key category for the history of architecture, which has been perceived positively for thousands of years. But in the 20th century prototypes began to be considered obsolete; avant-garde was focused on the complete refusal of them. In the second half of the 20th century the methodology of design tried to find a theoretical basis for the struggle against the prototypes. Have the prototypes been defeated? Should we fight against them? These are the questions that arise after reading “Design without prototypes”, a theoretical work by A. G. Rappaport, which was written 45 years ago.
Keywords: “design without prototypes”; architectural tradition; avant-garde; theory of architecture; methodology of design; prototype in architecture and design